การศึกษาสัณฐานกระบวนการเปลี่ยนแปลงลักษณะพื้นที่ริมน้ำ คลองบางลำพู - ศันสนีย์ ชูโชติถาวร (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Klong Bang Lamphu (Bang Lamphu canal) is a part of Klong Rop Krung (the canal which runs through the central district of Bangkok), which was an important historic canal in the Rattanakosin era). Klong Bang Lamphu was dug during the establishment of Bangkok as the capital city. It was listed as a heritage site by the Fine Arts Department. Klong Bang Lamphu was a part of the Thai life along the river and an important transport route since Bangkok was established. After that, the main transport route changed from the river to the land. Therefore, the river networks were cut off and the land was filled in. At present, people do not travel through the canal anymore, which influenced the evolution of Klong Bang Lamphu. The public area around Klong Bang Lamphu has been exploited in many ways. However, unlike in some developed countries, the city planners lacked the ability to coordinate the public development of the land with the preservation of the canals.The thesis studied the evolution of the public area around Klong Bang Lamphu, past and present. It investigated the relationships between the evolution of the public area, land transport routes, river transport routes, and city planning. The researcher studied the use of land from old maps and photos to draw a route map and a cross sectional map of Klong Bang Lamphu in the past. Also, the researcher drew a route map and a cross sectional map of Klong Bang Lamphu at present. Then, the use of land around Klong Bang Lamphu was divided into several categories and each was given a symbol to mark on the map. The researcher found several factors which helped to determine the course of the evolution of the Klong Bang Lamphu area.The usage of the land around Klong Bang Lamphu in the past can be classified into eight types. However, at present, there are ten types of land use and there have been twenty-five transformations. The transformation can be divided into four periods. The first period was between the establishment of Rattanakosin Kingdom and the building of the river banks. The second period was from the forming of Bangkok to the rise of the use of river banks for public and economic development. The third period was during the early modern period of Bangkok when the river banks were reconstructed by the locals. The fourth period lasted during the building of the identical permanent river banks by the government. In sum, the area around Klong Bang Lamphu at present is used as public utility and has not been developed to be multi-purpose.